AC susceptibility and hyperfine interactions of Mg-Ca ions co-substituted BaFe12O19 nanohexaferrites. Issue 8 (1st June 2019) - Almessiere, M.A.; Slimani, Y.; Güngüneş, H.; Ali, S.; Baykal, A.; Ercan, I.
Abstract: Magnesium and calcium co-substituted Ba M-type nanohexaferrite (NHFs) is fabricated via sol-gel auto-combustion technique. The phase formation was proved by XRD powder pattern, FESEM and HR-TEM. Magnetic properties of Ba1-2x Cax Mgx Fe12 O19 (x ≤ 0.1) NHFs investigated by Mossbauer Spectroscopy. The variations in line width, quadrupole splitting, isomer shift, the cation distribution of Ca 2+ and Mg 2+ ions and hyperfine magnetic field values were estimated. The AC magnetic susceptibility and ZFC-FC measurements were also performed for the Ba1-2x Cax Mgx Fe12 O19 ( x = 0.02 and 0.08) NHFs. The MFC -MZFC results do not show blocking temperature peak, indicating the ferrimagnetic (FM) behavior of prepared products. Different models including Neel-Arhenius (N-A), Vogel-Fulcher (V-F) and critical slowing down (CSD) were tested to evaluate the AC-magnetic susceptibility behaviors. It is demonstrated that the magnetic interactions are important for x = 0.02 NHFs.